Race against democracy: a case study of the Mail & Guardian during the early years of the Mbeki presidency, 1999-2002 - Steenveld, Lynette Noreen (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2007)
This thesis examines the 1998 complaint of racism against the Mail & Guardian, a leading exponent of South Africa's alternative press in the 1980s, and important contemporary producer of investigative journalism. The study is framed within a cultural studies approach, analysing the Mail & Guardian as constituted by a 'circuit of production': its social context, production, texts, and audiences. The thesis makes three main arguments. First, that the claim of racism cannot be understood outside of a consideration of both the changing political milieu, and subtle changes within the Mail & Guardian itself. Significant social changes relate to the reconfiguration of racial and class identities wrought by the 'Mbeki state'. Within the Mail & Guardian, the thesis argues for the importance of the power and subjectivity of the editor as a key 'factor' shaping the identity of the paper, evidenced in its production practices and textual outputs. In this regard, the thesis departs from a functionalist analysis of particular 'roles' within the newsroom, drawing instead on a post-structuralist approach to organisational studies. Based on this production and social context, the thesis examines key texts which deal with aspects of South Africa's social transformation, and which exemplify aspects of the Mail & Guardian's reporting which led to the complaint of racism by the Black Lawyers Association (BLA) and the Association of Black Accountants (ABASA). Their complaint was that the Mail & Guardian's reporting impugned the dignity of black people, and in so doing was a violation of their rights to dignity and equality which are constitutionally guaranteed. However, as freedom of the press is also guaranteed by the South African constitution, their complaint to the South African Human Rights Commission (SAHRC) resulted in public debate about these contending rights. My second argument relates to the jurisprudential approach to racism, and the related issue of affirmative action, which informed the complaint against the paper. Contrary to the 'normative', liberal approach to these issues, this thesis highlights Critical Race Theory as the jurisprudential basis for both the claimants' accusation of racism against the Mail & Guardian, and aspects of its implicit use in South African human rights adjudication. The thesis argues that in failing to recognise these different philosophical and political bases of legal reasoning, the media, including the Mail & Guardian, in reporting on these matters failed in their purported role of serving the public interest. The thesis concludes by applying Fraser's critique of Habermas's notion of a single, bourgeois public sphere to journalism, thereby suggesting ways in which the critiques of some of the Mail & Guardian's own journalists could be employed to enlarge its approach to journalism - giving voice to constituencies seldom heard in mainstream media.
Keywords: Mbeki, Thabo -- In mass media; Mail & Guardian; South African newspapers; Press -- South Africa; Press and politics -- South Africa; Journalism -- South Africa; Mass media and race relations -- South Africa; Racism in the press -- South Africa; Mass media -- Political aspects -- South Africa; South Africa -- Politics and government -- 20th century